(untitled) (Economic and Political Thought, 2018)
In the strategic transformation of the Polish defence policy in the post- Cold War period, three phases can be distinguished: breaking into strategic independence in the 1990s, integration with the Western security structures in the first decade of the 21st century and ongoing strategic adaptation to the neo-Cold War conditions of confrontation between Russia and the West. The transition from strategic incapacitation during the Warsaw Pact to renaissance and the development of a full-size, creative national strategic culture based on national interests was the main challenge in the first phase.. The main content of the second phase was, on the one hand, the transformation of its own security system in accordance with the ever-changing conditions of membership in NATO and the EU, and on the other hand, gaining experience in allied structures, including actively shaping them in accordance with Poland’s own national interests. The third phase began in 2014 in practice, when Russia’s aggression towards Ukraine and its confrontational policy led to the formation of neo-cold war conditions of security in its relations with the West. At the same time, the political change in Poland caused the breaking of strategic continuity in the functioning of the state and introduced additional risks to the external threats in the sphere of national security. Poland is currently facing the necessity of a strategic reconstruction of national security, both in the external dimension (relations with allies) and the internal one (restoring strategic continuity in the functioning of the state).